Cervical cytology service in Nigeria: providers’ perspective (2003)
It has been noted that efforts to organise an effective screening programme in developing countries will have to find adequate financial resources, develop the infrastructure, train the necessary manpower and elaborate surveillance mechanisms. In our study, we set out to determine (a) just how frequent is cervical cancer, to warrant the investment of funds in screening programmes; (b) what proportion of surveyed health facilities offer a cervical cytology screening programme; and (c) what basic facilities are currently available where such programmes exist? A pretested, self-completed questionnaire was sent to heads of department of obstetrics and gynaecology in public tertiary and secondary care hospitals in Nigeria as well as major mission hospitals. The response rate was 63%, monthly consultations included a mean of 114 (±11.7) new gynaecological patients and an average of 5 (4.7±0.8) cervical cancer cases. One-half of the institutions had a hospital-based cervical screening programme with an average of 27 patients being screened monthly. Finance was the main difficulty encountered in maintaining a screening service. Only four had a certified gynaecological oncologist. In conclusion, there is dismal utilization of available services and a dearth of trained specialists should any cervical cancer screening programme be considered.